1992
DOI: 10.1091/mbc.3.11.1295
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transforming growth factor-beta (TGF-beta) receptors on BeWo choriocarcinoma cells including the identification of a novel 38-kDa TGF-beta binding glycoprotein.

Abstract: Transforming growth factor-: (TGF-f) is a potential mediator of placental trophoblast functions, including differentiation, hormone production, endometrial invasion, and immunosuppression. Equilibrium binding and affinity-labeling assays were used to investigate the binding characteristics of TGF-41 and TGF-f2 on an established human choriocarcinoma trophoblastic cell line (BeWo). The equilibrium binding experiments indicated that the BeWo cells exhibited similar average affinities and total number of binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 57 publications
(50 reference statements)
3
9
0
Order By: Relevance
“…The first is a diffuse 400-to 150-kDa band that is characteristic of receptor type III. The other is a 50-kDa band that, due to its binding characteristics, was suggested by us to be a proteolytic fragment of receptor type III (34). We have now observed that both bands are specifically immunoprecipitated by an anti-peptide antibody directed against the C-terminal cytoplasmic domain of receptor type III (not shown).…”
Section: Resultsmentioning
confidence: 55%
“…The first is a diffuse 400-to 150-kDa band that is characteristic of receptor type III. The other is a 50-kDa band that, due to its binding characteristics, was suggested by us to be a proteolytic fragment of receptor type III (34). We have now observed that both bands are specifically immunoprecipitated by an anti-peptide antibody directed against the C-terminal cytoplasmic domain of receptor type III (not shown).…”
Section: Resultsmentioning
confidence: 55%
“…The mechanisms by which estrogens mediate their mitogenic effects on choriocarcinoma cell growth are unknown. However, the placenta expresses a variety of growth factors, including insulin growth factor-1 (IGF-1), transforming growth factor-ß (TGF-/3), and epidermal growth factor (EGF) and their respective binding proteins (Bhaumick et al, 1987;Morrish et al, 1987;Chen et al, 1990;Ringler and Strauss, 1990;Mitchell et al, 1992;Cao et al, 1994) and these growth factors play important roles in placental trophoblast function. For example, EGF promotes differentiation and secretion of hCG and hCS in trophoblastic cells (Marao et al, 1986;Morrish et al, 1987) and IGF-1 increases hCS production in term placenta (Bhaumick et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cell surface receptors of various sizes have been identified in cultured cells and tissues by cross-linking 125 I-labeled-TGF-b ( 125 I-TGF-b) to these molecules in the presence of bifunctional cross-linking reagents. These include type I (TbR-I, MW$53,000), type II (TbR-II, MW$70,000), type III (TbR-III, MW$ 280,000-370,000), type IV (TbR-IV, MW$ 60,000), type V (TbR-V, MW$400,000), and type VI (TbR-VI, MW$180,000) receptors as well as several membrane-associated binding proteins (MW$38,000) [O'Grady et al, 1991a;Mitchell et al, 1992;Segarini, 1993;Massague, 1998;Moustakas et al, 2002]. TbR-I and TbR-II are Ser/Thr-specific protein kinases and are believed to be primarily responsible for TGF-b-induced cellular responses [Heldin et al, 1997;Massague, 1998;Roberts, 1998].…”
mentioning
confidence: 99%
“…TbR-V coexpresses with TbR-I, TbR-II, and TbR-III in all normal cell types studied thus far [O'Grady et al, 1991a,b] and also serves as the insulin-like growth factor binding protein-3 (IGFBP-3) receptor, mediating IGF-independent growth inhibition by IGFBP-3 in responsive cells [Leal et al, 1997[Leal et al, , 1999Wu et al, 2000]. TbR-VI and other membrane-associated TGF-b binding proteins are expressed only in specific cell types [Mitchell et al, 1992;Segarini, 1993].…”
mentioning
confidence: 99%